Про сучасний стан розвитку методів ідентифікації об’єктів на зображенні - Бабочкін, О. О. (ХНУРЕ, 2021)
Methods for analyzing and identifying the shape of graphic objects have been and remain a very urgent scientific problem for solving a wide range of various theoretical and national economic problems. This is one of the most promising computer and software sciences is computer vision. A lot of existing works in this area can be divided into several directions, each of which has its own characteristics. Finding objects in a picture is most likely the most important area of computer vision. Current state of evelopment of identification is described in this work.